Implementation of restorative justice based on Aceh qanun number: 9 of 2008 on the settlement of the crime of persecution In Gampong Lam Rukam sub district Peukan bada Aceh Besar Regency - M. Ryan citra Yudha; Yasmirah Mandasari Saragih (International Journal of Society and Law, 2024)
Law enforcement encompasses three main elements: legal certainty, utility, and justice. Criminal law aims to realize justice in society by resolving criminal cases and protecting human rights. However, law enforcement processes often focus on punishing offenders without adequately addressing the victims' physical and psychological losses. The Indonesian Police implement strategic policies to achieve justice through restorative justice, as outlined in Police Regulation Number 6 of 2019 and Circular Letter Number SE/8/VII/2018. This approach aims to restore the victims' conditions to their original state or as close as possible. In Aceh, customary institutions are authorized to resolve community issues, supported by the Joint Decree between the Aceh Government, Aceh Police Chief, and Aceh Customary Council. Qanun Aceh Number 9 of 2008 also regulates the resolution of disputes through customary courts at the village and mukim levels. Customary judicial bodies in Aceh, such as Keuchik, Tuha Peut, Imeum Meunasah, ulama, and traditional leaders, function to resolve disputes peacefully. This study, titled "Implementation of Restorative Justice Based on Qanun Aceh Number 9 of 2008 in Resolving Assault Crimes in Gampong Lam Rukam, Peukan Bada District, Aceh Besar Regency," aims to review the legal basis for restorative justice for assault crimes in Indonesia and examine its implementation in Gampong Lam Rukam.